The effects of human menstrual blood stem cells‐derived granulosa cells on ovarian follicle formation in a rat model of premature ovarian failure. Issue 6 (23rd December 2018) - Manshadi, Marjan D.; Navid, Shadan; Hoshino, Yumi; Daneshi, Erfan; Noory, Parastoo; Abbasi, Mehdi
Abstract: Many studies have reported that human endometrial mesenchymal stem cells (HuMenSCs) are capable of repairing damaged tissues. The aim of the present study was to investigate the effects of HuMenSCs transplantation as a treatment modality in premature ovarian failure (POF) associated with chemotherapy‐induced ovarian damage. HuMenSCs were isolated from menstrual blood samples of five women. After the in vitro culture of HuMenSCs, purity of the cells was assessed by cytometry using CD44, CD90, CD34, and CD45 FITC conjugate antibody. Twenty‐four female Wistar rats were randomly divided into four groups: negative control, positive control, sham, and treatment groups. The rat models of POF used in our study were established by injecting busulfan intraperitoneally into the rats during the first estrus cycle. HuMenSCs were transplanted by injection via the tail vein into the POF‐induced rats. Four weeks after POF induction, ovaries were collected and the levels of Amh, Fst, and Fshr expression in the granulosa cell (GC) layer, as well as plasma estradiol (E2) and progesterone (P4) levels were evaluated. Moreover, migration and localization of DiI‐labeled HuMenSCs were detected, and the labeled cells were found to be localized in GCs layer of immature follicles. In addition to DiI‐labelled HuMenSCs tracking, increased levels of expression of Amh and Fshr and Fst, and the high plasma levels of E2 and P4 confirmed that HuMenSC transplantation had a significant effect on follicle formation and ovulation in the treatment group compared with the negative control (POF) group. Abstract : Our findings demonstrated that HuMenSCs have improved restorative effects on ovarian function. ELISA and real time PCR techniques were used to evaluate the various parameters in our study.